Investigating antemortem, perimortem and postmortem injuries: forensic implication (Bangladesh Journal of Medical Science, 2021)
Context:Skeletal injuries discovered from human remains are classified into antemortem,perimortem and postmortem. Studies that documents injuries of various skeletal elementsis of vital importance to forensic anthropologist.Aim: This study investigated antemortem,perimortem, postmortem and other injuries caused by various instruments among skeletal elements.Methodology: A total of 200 bones of unknown age and gender were studied.Injuries were interpreted based on basic features specific to them and each was described andphotographed. Chisquare test was used to show association between skeletal elements andtime of injuries. Statistical evaluation was done using SPSS 20 Software Version. Significance was accepted at p